2006
DOI: 10.1007/s00264-006-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Massive allografts in tumour surgery

Abstract: We offer our personal experience of the use of massive bone allografts after tumour resection. We demonstrate the long-term results from 71 patients (72 allografts) operated on between 1961 and 1990. The long-term survival rate in osteoarticular and intercalary grafts is around 60%. Fractures of the graft can be salvaged in most cases. Infection leads to the removal of the graft in almost all cases. Factors influencing the survival, remodelling and complications of the grafts are discussed. The regime of cryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Some have reported that 16 out of 24 patients (67%) suffered local recurrence within the first two years, six (25%) suffered recurrence between two and five years later and two (8.3%) suffered recurrence more than five years later. Therefore, postoperative follow-up examinations of GCT patients are essential for at least the first five years [11][12][13][14], as recommended by Eckardt and Grogan [5,7,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have reported that 16 out of 24 patients (67%) suffered local recurrence within the first two years, six (25%) suffered recurrence between two and five years later and two (8.3%) suffered recurrence more than five years later. Therefore, postoperative follow-up examinations of GCT patients are essential for at least the first five years [11][12][13][14], as recommended by Eckardt and Grogan [5,7,12].…”
Section: Discussionmentioning
confidence: 99%
“…While single extended curettage performed carefully by an experienced orthopaedic oncologist offers a good chance of eliminating the disease, the results are not so predictable in aggressive grade III tumours [4,13,14]. We recommend that treatment with curettage for grade I and II giant cell tumours offers a very good (90%) chance of cure.…”
Section: Discussionmentioning
confidence: 99%
“…Complications include nonunion, fractures, slow incorporation of the allograft and possibility of transmitting infectious diseases [11,17]. Furthermore, allografts are not easily procurable in most countries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of allografts, alloprosthetic composites and prosthetic replacements to reconstruct the proximal humerus after tumour resection and associated complications have been well described [5][6][7][8][9]11]. However, extensive tumours of the humerus, large tumours of the diaphysis and local recurrent disease after limb-salvage surgery present unique problems with respect to reconstruction options.…”
Section: Introductionmentioning
confidence: 99%